The migraineur's brain networks: Continuous resting state fMRI over 30 days. (December 2020) - Schulte, Laura H; Menz, Mareike M; Haaker, Jan; May, Arne
Objective: The aim of the current study was to identify typical alterations in resting state connectivity within different stages of the migraine cycle and to thus explore task-free mechanisms of headache attack generation in migraineurs. Background: Recent evidence in migraine pathophysiology suggests that hours and even days before headache certain changes in brain activity take place, ultimately leading to an attack. Here, we investigate changes before headache onset using resting state functional magnetic resonance imaging (fMRI). Methods: Nine episodic migraineurs underwent daily resting state functional magnetic resonance imaging for a minimum period of 30 consecutive days, leading to a cumulative number of 282 total days scanned. Thus, data from 15 spontaneous headache attacks were acquired. This allows analysing not only the ictal and the interictal phase of migraine but also the preictal phase. ROI-to-ROI (region of interest) and ROI-to-voxel connectivity was calculated over the migraine cycle. Results: Within the ROI-to-ROI analysis, the right nucleus accumbens showed enhanced functional connectivity to the left amygdala, hippocampus and gyrus parahippocampalis in the preictal phase compared to the interictal phase. ROI-to-voxel connectivity of the right accumbens with the dorsal rostral pons was enhanced during the preictal phase compared to interictally. Regarding custom defined ROIs, the dorsal pons was ictally functionally more strongly coupled to the hypothalamic area than interictally. Conclusions: This unique data set suggests that particularly connectivity changes in dopaminergic centres and between the dorsal pons and the hypothalamus are important within migraine attack generation and sustainment.